2022
DOI: 10.1093/femsml/uqac025
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of membrane vesicles in Alteromonas macleodii indicates potential roles in their copiotrophic lifestyle

Abstract: Bacterial membrane vesicles (MVs) are abundant in the oceans, but their potential functional roles remain unclear. In this study we characterized MV production and protein content of six strains of Alteromonas macleodii, a cosmopolitan marine bacterium. A. macleodii strains varied in their MV production rates, with some releasing up to 30 MVs per cell per generation. Microscopy imaging revealed heterogenous MV morphologies, including some MVs aggregated within larger membrane structures. Proteomic characteriza… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 94 publications
0
7
0
Order By: Relevance
“…Interestingly, the most abundant proteins observed were identified as TonB-dependent receptors (TBDR), accounting for nearly half of the proteins detected. TBDR enrichment has been previously reported in OMVs of several Gram-negative bacteria (Veith et al ., 2015; Zakharzhevskaya et al ., 2017; Dhurve et al ., 2022; Fadeev et al ., 2023). TBDRs are outer membrane-associated proteins that bind and mediate the energy-dependent movement of siderophores and various nutrients, including carbohydrates that are too large to be taken up via transmembrane diffusion across the outer membrane (Silale and Van Den Berg, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the most abundant proteins observed were identified as TonB-dependent receptors (TBDR), accounting for nearly half of the proteins detected. TBDR enrichment has been previously reported in OMVs of several Gram-negative bacteria (Veith et al ., 2015; Zakharzhevskaya et al ., 2017; Dhurve et al ., 2022; Fadeev et al ., 2023). TBDRs are outer membrane-associated proteins that bind and mediate the energy-dependent movement of siderophores and various nutrients, including carbohydrates that are too large to be taken up via transmembrane diffusion across the outer membrane (Silale and Van Den Berg, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of research on OMVs has been done on pathogenic bacteria due to the capacity of OMVs to carry and deliver virulence factors and toxins into host cells (O'Donoghue and Krachler, 2016;Lynch and Alegado, 2017;Caruana and Walper, 2020). However, the role of OMVs in marine and other environments has been increasingly recognized, likely playing crucial roles in nutrient processing and ecological interacXons (Frias et al, 2010;Biller et al, 2014Biller et al, , 2022Fischer et al, 2019;Fadeev et al, 2023).…”
Section: Introduc:onmentioning
confidence: 99%
See 1 more Smart Citation
“…In a subsequent study, Biller et al demonstrated that this packaging of DNA in marine microbes is not homogeneous between EVs for five different evaluated strains . Since this initial report, more recent reports have suggested that EVs from seawater may be involved in the uptake of iron and phosphorus, the mitigation of toxic reactive oxygen species, the formation of biofilms, and the catalysis of extracellular biochemical reactions. , …”
Section: Extracellular Vesicles As Functional Colloids In the Environ...mentioning
confidence: 99%
“…126 Since this initial report, more recent reports have suggested that EVs from seawater may be involved in the uptake of iron and phosphorus, the mitigation of toxic reactive oxygen species, the formation of biofilms, and the catalysis of extracellular biochemical reactions. 127,128 Molecules present as cargo associated with EVs may be potentially persistent and able to travel longer distances than molecules not associated with EVs. A study of EVs in feces showed that vesicles can help to preserve RNA from degradation.…”
Section: Functions Of Evs Asmentioning
confidence: 99%